2022
DOI: 10.7717/peerj.12705
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations and co-occurrence networks of bacterial communities in the water and sediment of artificial habitat in Laoshan Bay, China

Abstract: Marine bacteria in the seawater and seafloor are essential parts of Earth’s biodiversity, as they are critical participants of the global energy flow and the material cycles. However, their spatial-temporal variations and potential interactions among varied biotopes in artificial habitat are poorly understood. In this study, we profiled the variations of bacterial communities among seasons and areas in the water and sediment of artificial reefs using 16S rRNA gene sequencing, and analyzed the potential interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Lee, et al [ 12 ] identified the presence of Proteobacteria, followed by Chloroflexi, Bacteroidetes, Acidobacteria, and Firmicutes in sediments in the Yellow Sea. In the sediments originating from Laoshan Bay (China), the bacterial community was dominated (>10%) by the phyla Proteobacteria, Desulfobacterota, and Acidobacteria [ 13 ]. It was also emphasized that the biodiversity of urban ponds, expressed by species richness, appears to be generally lower than in rural ponds [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee, et al [ 12 ] identified the presence of Proteobacteria, followed by Chloroflexi, Bacteroidetes, Acidobacteria, and Firmicutes in sediments in the Yellow Sea. In the sediments originating from Laoshan Bay (China), the bacterial community was dominated (>10%) by the phyla Proteobacteria, Desulfobacterota, and Acidobacteria [ 13 ]. It was also emphasized that the biodiversity of urban ponds, expressed by species richness, appears to be generally lower than in rural ponds [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…What is more, it was suggested that ponds are highly diverse but understudied systems that could benefit from eDNA monitoring [ 15 ]. Usually, assessment of pond biodiversity is regarded as costly, time-consuming, and dependent on taxonomic expertise [ 13 , 16 ]. Nevertheless, a culture-independent technique was used in this study to identify the highest possible number of bacteria capable of living in the bottom sediments of a pond intended for organic king carp culture.…”
Section: Introductionmentioning
confidence: 99%